The Influence of Storytelling Methods in Improving the Religious Character of SDN 015 Rambah Students - Nismar, Nismar; Jazrizal, Jazrizal; Supriyadi, Supriyadi (Indonesian Journal of Basic Education, 2024)
Students often consider religious learning in elementary schools (SD) less attractive, so religious values are difficult to understand and internalize properly. One approach that can be used to overcome this problem is the storytelling method, which is considered more effective in conveying moral messages and religious values. This study aims to analyze the influence of storytelling methods on improving elementary school students' religious character. This study uses the Classroom Action Research method, which is carried out in two cycles. Storytelling is applied by delivering stories of prophets and inspirational Islamic figures as a learning medium. Data were collected through observation sheets to measure students' responses and understanding of religious values, as well as students' reflections to see the extent of changes in attitudes after applying the storytelling method. After using storytelling, the study results show a significant increase in students' understanding and application of religious values. Success indicators can be seen from increased student participation in discussions, knowledge of moral values in stories, and behavioral changes in a more positive direction in daily life. Thus, it can be concluded that the storytelling method effectively improves the religious character of elementary school students and can be a more interesting and meaningful learning alternative in religious education.